1999
DOI: 10.1590/s0034-89101999000400005
|View full text |Cite
|
Sign up to set email alerts
|

Assessing morbidity in the paediatric community

Abstract: VOLUME 33 NÚMERO 4 AGOSTO 1999© Copyright Faculdade de Saúde Pública da USP. Proibida a reprodução mesmo que parcial sem a devida autorização do Editor Científico. Proibida a utilização de matérias para fins comerciais. All rights reserved. Morbidity information is easily available from medical records but its scope is limited to the population attended by the health services. Information on the prevalence of diseases requires community surveys, which are not always feasible. These two sources of information r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
2
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
1
4
2
2
Order By: Relevance
“…23 In addition, although the incidence of diarrhea and gastroenteritis (7.1%) among HIV-1-uninfected infants in our study, who did not have the benefits of breastfeeding, 24,25 was similar to the estimates for Brazilian infants born to HIV-1-uninfected mothers, 26 it was much lower than that (35%) found for infants Ͻ6 months of age in Brazilian urban slums 27 and that (30%) for HIV-1-uninfected infants from South Africa. 28 All HIV-1-exposed infants enrolled in the NISDI Perinatal Study had replacement feeding ensured and special attention regarding hygienic measures for formula preparation, which might have affected positively the incidence and severity of diarrhea but not oral candidiasis among these infants.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…23 In addition, although the incidence of diarrhea and gastroenteritis (7.1%) among HIV-1-uninfected infants in our study, who did not have the benefits of breastfeeding, 24,25 was similar to the estimates for Brazilian infants born to HIV-1-uninfected mothers, 26 it was much lower than that (35%) found for infants Ͻ6 months of age in Brazilian urban slums 27 and that (30%) for HIV-1-uninfected infants from South Africa. 28 All HIV-1-exposed infants enrolled in the NISDI Perinatal Study had replacement feeding ensured and special attention regarding hygienic measures for formula preparation, which might have affected positively the incidence and severity of diarrhea but not oral candidiasis among these infants.…”
Section: Discussionsupporting
confidence: 74%
“…Our findings of any respiratory infection for 150 of the studied infants (32.5%) was higher than that in a Brazilian community-based study (20%). 26 Although there is the possibility of recall bias with respect to upper respiratory tract infections, this is much less likely for lower respiratory tract infections. Recent data from community based-studies regarding lower respiratory tract infection rates in normal, HIV-1-unexposed infants are not available.…”
Section: Discussionmentioning
confidence: 99%
“…Although a control group of infants born to HIV-uninfected mothers was not available in our study, a comparison with the most recent available data from a Brazilian community-based study 15 showed that the frequency of LRTI in the NISDI cohort of HIV-uninfected infants was similar to the 20% prevalence of all respiratory tract infections (RTIs) in infants. However, this study 15 did not differentiate between LRTI and upper RTI.…”
Section: Discussionmentioning
confidence: 79%
“…These same diseases showed the highest prevalence among children aged one to four years; however, the frequency of infectious diseases increased. 9 The English study 12 of symptoms and medical appointments among preschool children found that the most frequent symptoms across three age groups (< six months; six to 17 months; 18 to 29 months) were those related to the respiratory system (cold and cough), the frequency of which increases with age. Symptoms related to alimentary tract and metabolism (cramps, diarrhea, and vomiting) were more frequent among younger children.…”
Section: Discussionmentioning
confidence: 99%